Cybercrime dan Cybersecurity pada Fintech: Sebuah Tinjauan Pustaka Sistematis - Moh Riskiyadi; Alexander Anggono; Tarjo (IPB University, 2021)
This study is intended to determine the cybercrime challenges faced by the fintech industry as well as anticipatory actions in the form of cybersecurity to overcome these challenges. This study employs a systematic literature review method from various articles discussing cybercrime and cybersecurity in fintech that were published in reputable online databases. The findings indicate that cybercrime problems in fintech consist of cybercrime regulations that are not strict, data and information theft, and intellectual property theft in which impacting on the reputation of fintech. Cybersecurity as an attempt to tackle cybercrime in fintech can be performed through proactive action, strengthening regulations, and establishing a reliable cybersecurity framework or procedure. The implications of this research are as an additional reference for academics, practitioners, regulators, and fintech actors related to the fast pace development of cybercrime and cybersecurity in fintech. The limitation of this study is that it only provides an overview and elaborate the results of prior studies instead of provide a further analysis of the relationship between the articles discussed. Recommendations for further research are to increase the scope of the articles studied or apply other literature review methods or conduct empirical research to confirm the results of this study.